2017
DOI: 10.1103/physrevlett.119.106602
|View full text |Cite
|
Sign up to set email alerts
|

Negative Longitudinal Magnetoresistance from the Anomalous N=0 Landau Level in Topological Materials

Abstract: Negative longitudinal magnetoresistance (NLMR) is shown to occur in topological materials in the extreme quantum limit, when a magnetic field is applied parallel to the excitation current. We perform pulsed and DC field measurements on Pb1-xSnxSe epilayers where the topological state can be chemically tuned. The NLMR is observed in the topological state, but is suppressed and becomes positive when the system becomes trivial. In a topological material, the lowest N=0 conduction Landau level disperses down in en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 51 publications
3
42
0
Order By: Relevance
“…[9]). This lifting can lead to a better fitting to a recent experiment on the topological insulator material Pb 1−x Sn x Se [8], which shows an unexpected suppression of the resistance in strong magnetic fields, as shown in Figs. 1 (c) and 1 (d).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…[9]). This lifting can lead to a better fitting to a recent experiment on the topological insulator material Pb 1−x Sn x Se [8], which shows an unexpected suppression of the resistance in strong magnetic fields, as shown in Figs. 1 (c) and 1 (d).…”
supporting
confidence: 55%
“…Experimental implications -Although Pb 1−x Sn x Se is claimed to be a topological insulator, the interpretation in Ref. [8] adopted a theory for Weyl semimetal in delta scattering potentials [12,13], where the spinor wave function of the lowest Landau band takes the form |0, k x , k z = 0 |0 |k x , k z .…”
mentioning
confidence: 99%
“…The negative MR is widely believed to be a signature showing that a topological semimetal can host the chiral anomaly, that is, the conservation of chiral current is violated as a result of the quantization [14][15][16]. However, in other systems where the chiral anomaly is not well defined, e.g., in topological insulators, a negative MR has also been observed and has created great confusion [17][18][19][20][21][22]. In this Letter, we present a quantitative study on the MR of 3D topological insulators.…”
mentioning
confidence: 99%
“…Nevertheless, in topological insulators, where the chiral anomaly is not well defined in the momentum space, a negative magnetoresistance can also be observed. This results in great confusion [109][110][111][112][124][125][126] on the explanation of the negative magnetoresistance. Lately, it is found that the chiral anomaly in real space can be defined in a quantum spin Hall insulator [127].…”
Section: Weak Field: Negative Magnetoresistance In Topological Imentioning
confidence: 99%
“…Ref. [10] shows that this mechanism is large enough in topological insulators as those observed in the experiments, where the relative magnetoresistance can exceed -1% in a parallel magnetic field of several Tesla [109][110][111][112][124][125][126].…”
Section: A Anomalous Velocitymentioning
confidence: 99%